Tocilizumab-treated convalescent COVID-19 patients retain the cross-neutralization potential against SARS-CoV-2 variants - Chauvin, Camille; Levillayer, Laurine; Roumier, Mathilde; Nielly, Hubert; Roth, Claude; Karnam, Anupama; Bonam, Srinivasa Reddy; Bourgarit, Anne; Dubost, Clément; Bousquet, Aurore; Le Burel, Sébastien; Mestiri, Raphaële; et al. (iScience, 2023)
Although tocilizumab treatment in severe and critical coronavirus disease 2019 (COVID-19) patients has proven its efficacy at the clinical level, there is little evidence supporting the effect of short-term use of interleukin-6 receptor blocking therapy on the B cell sub-populations and the cross-neutralization of SARS-CoV-2 variants in convalescent COVID-19 patients. We performed immunological profiling of 69 tocilizumab-treated and non-treated convalescent COVID-19 patients in total. We observed that SARS-CoV-2-specific IgG1 titers depended on disease severity but not on tocilizumab treatment. The plasma of both treated and non-treated patients infected with the ancestral variant exhibit strong neutralizing activity against the ancestral virus and the Alpha, Beta, and Delta variants of SARS-CoV-2, whereas the Gamma and Omicron viruses were less sensitive to seroneutralization. Overall, we observed that, despite the clinical benefits of short-term tocilizumab therapy in modifying the cytokine storm associated with COVID-19 infections, there were no modifications in the robustness of B cell and IgG responses to Spike antigens. [Display omitted] •SARS-CoV-2-specific IgG1 titers depended on disease severity but not on tocilizumab•No major impact of tocilizumab on the B cell subsets and SARS-CoV-2-specific IgG1•Tocilizumab does not alter plasma virus neutralization capacity for SARS-CoV-2 VOCs Health sciences; Virology; Treatment; Immunology.